Imagined communities, divided realities : engaging the apartheid past through 'healing of memories' in a post-TRC South Africa - Kayser, Undine (Social Anthropology, 2016)
The dissertation argues that, in the attempt to build a shared democratic culture among ordinary citizens in post-apartheid South Africa, insufficient attention has been paid to transformations of interpersonal domains. The dissertation examines the process and effects of the Healing of Memories (HOM) project in Cape Town. HOM is a civil society initiative established in 1996 to facilitate storytelling workshops between South Africans, previously divided on the basis of race and class. Critiquing reconciliation discourses in South Africa, in particular that generated by the Truth and Reconciliation Commission (TRC), the research points the importance of lived, local, ongoing encounters between ordinary people who take cognizance of the apartheid past. Given the context of apartheid's stark socio-spatial legacies, the dissertation argues that there are few spaces in and processes through which ordinary social actors can explore their respective subject positions under apartheid and grapple with the emerging subjectivities of the post-apartheid sphere. HOM offered face-to-face encounters with the former racial 'Other'. In an immediate and participatory process of witnessing each other's personal memories of apartheid, participants' conventional understandings of self, 'Other' and history were unsettled, leading participants to 'make connections' between past and present, between the personal and the political, and between their own and other's expectations and hopes for change. The dissertation argues that this led to the forging of a temporary 'community of sentiment', based on a core set of 'new' social skills: response-ability, conflict-ability and sociability. The fraught experiential-emotional dimension of the encounters revealed some of the underlying 'structures of feeling' and their impact on the 'formations of relationship', which continuously hinder the search for new and meaningful ways of being social. The encounters produced the imaginative ground for new forms of inter-subjectivity in the post-apartheid sphere. Those who engaged in the process regularly were able to make substantial changes in their interpersonal relations. In its discussion of HOM. as a healing intervention in a post-authoritarian state, the discussion also draws on the author's experiences of post-Holocaust Germany and extensive library research in this field.